An ‘authentic’ Aboriginal product: State marketing and the self-fashioning of Indigenous experiences to Chinese tourists - Boag, Courtney J. (The Australian journal of anthropology, 2020)
China's burgeoning outbound tourist market has become a priority for Australian tourism, with national and state tourism reports advocating for ‘China-ready’ marketing, policy and planning and increased industry training around Chinese consumer behaviour and preferences to capitalise on this market. However, studies demonstrate that Chinese tourists are generally not interested in Indigenous tourism experiences. Nevertheless, the state of Victoria is adamant about investing in Indigenous-themed tourism products which are considered appropriate for Chinese preferences in an attempt to attract tourists from this growing inbound market. This article presents a review of relevant state government policies relating to Indigenous tourism alongside a case study of the tourism experiences developed and provided by Gunditjmara people along the Budj Bim Cultural Landscape in southwest Victoria. We demonstrate the ways that notions of ‘authenticity’ continue to shape, and constrain, Indigenous economic engagement and participation via tourism, and discuss the impact of these notions on the provision of Indigenous tourism products and experiences for Chinese and other visitors. We argue that the marketing of Gunditjmara tourism to fluctuating market demand highlights the arbitrariness of Australian governments' policies with respect to Indigenous development, and call for policymakers to focus renewed attention on the local aspirations of Indigenous entrepreneurs.